Forecast of brine blowout zones in the Amu Darya basin and analysis of brine blowout in oil and gas fields - Deryaev Annaguly (Glasnik Srpskog Geografskog Društva)
The purpose of this study is to forecast possible brine blowout zones in the Amu Darya basin and further analyse these manifestations in oil and gas fields to assess their potential for hydrocarbon extraction. The study examined the geological structure through the assessment of lithological and facies maps and sections, the geochemical content of salts and isotopic composition of waters, and hydrogeological methods, including analysis of groundwater regime and well drilling. The obtained data deepened the understanding of the region’s geological structure and identified potential hydrocarbon concentration zones, which are crucial for further extraction and utilisation of these resources. Specifically, potential brine blowout zones were determined through analysis of structural features and rock composition. This is critical for subsequent exploration and identification of deposits with high hydrocarbon extraction potential. In addition, the study provided a detailed characterisation of depressions and their physical properties, including viscosity, density, and thermal conductivity. This analysis led to a deeper understanding of the nature of depression formations and the development of more effective methods for their extraction and processing. The data analysis methods ensure more accurate and reliable results, help-ing not only to determine optimal development points for deposits but also to reduce risks associated with costly drilling and extraction operations. The obtained findings have practical value for the oil and gas industry, contributing to improving the efficiency of hydro-carbon extraction and processing processes, which are essential for the sustainable development of the industry and ensuring regional energy security.